POTENTIAL MARKET CAPACITY AS THE BASIS FOR THE DEVELOPMENT OF ORGANIC PRODUCTION IN THE RUSSIAN FEDERATION - Elena Alexandrovna ALESHINA; Anna Alexandrovna LEKSINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The promotion of a healthy lifestyle and objective necessity stimulate a significant growth in demand for organic products around the world. Despite the relevance, demand, and a large number of theoretical and applied research, the opportunities and resource potential of the Russian Federation in this area of agribusiness have not yet been fully identified. As part of our research, was formed interdisciplinary fundamental platform for developing the theory of organic food market. As a result, we determined the elements of scientific methodology (theories, principles, factors, methods) of its functioning, which allowed justifying the potential capacity of the consumer market of organic food in Russia. The calculation was made taking into account dietary intake of food that meet the present-day requirements of healthy nutrition, heterogeneity of consumer preferences, price gap for the staple conventional and organic products in retail and price variance for the latter. Our research is addressed to the world business community operating in the organic food market and industry research institutions.